The Fallacy of the European Satrapy - Sarakinski, Vojislav (Živa Antika, 2010)
This paper deals with the status of Thrace and Macedonia within the royal administration of the Persian Empire. The scholar views expressed so far are opposing and mutually exclusive. thus making it very difficult to attain a common ground between them. The complete corpus of information on the satrapies comes from the Persian administrative documents and from the extant Greek sources. However. the meaning of the word "satrapy" in the Greek sources is very vague, and moreover, this technical term is nowhere to be found in the Persian documents. This calls for a re-thinking and re-examination of the term "satrapy" as a terminus technicus, as well as for a broader analysis of the mechanisms of satrapal actions and their place within the Persian administrative and fiscal framework. As things stand, the term "satrap" should be analysed only in its first, basic meaning, "protector of the King/Empire" - a status that did not hinder the possibility of holding other local or foreign offices or honours.